Beats not beatings: the rise of hip hop criminology - Nocella, Anthony J. (Hip Hop studies and activism, 2024)
"Beats Not Beatings: The Rise of Hip Hop Criminology is a powerful radical intersectional scholarly-activist collection of liberation-based articles by "Mic" Crenshaw, Chandra Ward, Maurece Graham, Daniel White Hodge, Anthony J. Nocella II, Antonio Quintana, Andrea N. Hunt, Tammy D. Rhodes, Kenneth Culton, Andre Douglas Pond Cummings, Victor Mendoza, Adam de Paor-Evans, Lenard G. Gomes, Elloit Cardozo, and Tasha Iglesias that center marginalized and oppressed stories and experiences. This book emerged out of the Black Lives Matter and prison abolition movements. This collection challenges state violence as well as racist and classiest laws such as the school to prison pipeline, redlining, three strikes, mandatory minimums, truancy, felons cannot vote, check the box, and curfew. This thought-provoking insightful text demands that those affected by the criminal justice system should be leading the conversation on how it is broken, managed, and needs to be transformed. Critical theorist Anthony J. Nocella II, an innovative intersectional public intellectual, pushes educators and society to make connections and think outside the box on how Hip Hop has always had the answers on how to dismantle racism and classism by the U.S. criminal justice system. This book explains how Hip Hop brilliantly since day one has the answer to ending violence and crime in society, it is time to listen, get in where you fit in, or get out of the way"